The role of supine imaging in assessing failure of pelvic compensation and its impact on surgical outcomes in patients with adult spinal deformity - Dongfan Wang; Wei Wang; Yu Wang; Chao Kong; Shuaikang Wang; Xiaolong Chen; Shibao Lu (Journal of Orthopaedic Surgery and Research)
Abstract Aims This study aims to investigate the impacts of failure of pelvic compensation (FPC), as determined by variations in spinopelvic alignment during the transition from the supine to the upright position, on surgical outcomes in patients with adult spinal deformity (ASD). Methods A total of 125 ASD patients who underwent posterior correction surgery with a minimum follow-up of two years were enrolled. Radiographic outcomes, including thoracic kyphosis, lumbar lordosis, sacral slope (SS), pelvic tilt (PT), pelvic incidence, T1-pelvic-angle and sagittal vertical axis (SVA), were measured on lateral whole-spine radiographs. Postoperative realignment was assessed using the sagittal age-adjusted score (SAAS). Patient-reported outcomes were collected through Scoliosis Research Society-22R (SRS-22R) questionnaire, alongside data on minimum clinically important difference (MCID) achievement. The incidence of proximal junctional kyphosis (PJK) following surgery was also recorded. Based on the calculated minimum detectable change of SS, FPC was defined as the change in SS of less than 3.9° between supine and upright positions. Patients were divided into the pelvic compensation (PC) cohort and the FPC cohort. Results Eighty-eight patients were categorized into the PC cohort and 37 into the FPC cohort. Postoperatively, patients with FPC exhibited significantly lower PT (22.44° vs. 28.57°, p <.001) and higher SVA (57.49 mm vs. 32.57 mm, p =.008) than PC patients. Additionally, the SRS-22R subtotal score was lower in the FPC group (3.68 vs. 3.89, p =.035), and the proportion of MCID achievement in SRS-22R was significantly reduced (45.95% vs. 65.91%, p =.038). While the incidence of PJK was higher in FPC patients, this difference was not significant (40.54% vs. 29.55%, p =.232). Correcting to SAAS matching standard was associated with a reduced risk of PJK (OR 6.50, 95%CI 1.18–35.84) and increased likelihood of achieving MCID (OR 4.50, 95%CI 1.05–19.22) in ASD patients with FPC. Conclusion ASD patients with preoperative FPC are more likely to experience worse patient-reported outcomes and a higher incidence of mechanical complications following corrective surgery. To optimize surgical outcomes in these patients, individualized preoperative planning aligned with the SAAS criteria may be particularly beneficial.